Biodegradable nanoparticles bearing amine groups as a strategy to alter surface features, biological identity and accumulation in a lung metastasis model. Issue 37 (5th September 2018) - Esposito, Diletta; Conte, Claudia; Dal Poggetto, Giovanni; Russo, Annapina; Barbieri, Antonio; Ungaro, Francesca; Arra, Claudio; Russo, Giulia; Laurienzo, Paola; Quaglia, Fabiana
Abstract : A panel of PCL-based amine NPs is prepared, tested for stability in different biologically-relevant media and intravenously injected in a mice model of lung metastasis. Abstract : Polymer-based nanoparticles (NPs) with a cationic charge have emerged recently as a potent nanotool due to their unique ability to penetrate deeply inside tumor tissue and to interact preferentially with the plasma membrane of cancer cells. In this paper, we propose a general strategy to obtain biodegradable cationic NPs of poly(ε-caprolactone) (PCL) based on an amine terminated PCL (NH2 -PCL4.2k ) or its mixture with monomethoxypoly(ethylene glycol)–PCL (mPEG1k –PCL4k ). Positively-charged NPs were obtained, switching to net negative values through adsorption of low molecular weight hyaluronan. NPs exposing both amine and PEG groups on the surface showed a larger fixed aqueous layer thickness as compared to fully PEGylated NPs, suggesting that PEG conformation/localization is affected by the presence of amino groups. The stability of the positively-charged NPs was affected by the presence of ions, while interaction with the human plasma protein pool indicated time-dependent protein corona formation imparting an overall negative charge. NP-induced haemolysis was low, while cytotoxicity against A549 and Calu-3 lung cancer cell lines was cell-specific as well as dose and time-dependent. Finally, the presence of amino groups greatly changed the in vivo biodistribution of the NPs in tumor-bearing mice (lung colonization of B16F10 cancer cells) allowing the amine/PEGylated NPs to accumulate mainly at the target organ. Overall, this study demonstrates that NPs with a mixed amine/PEGylated surface exhibit a peculiar biological identity that alters their interaction with the bioenvironment and are thus worthy of further investigation in the delivery of chemotherapeutics.